(untitled) (Revista Horizontes de Linguistica Aplicada, 2012)
Research articles in national and international journals provide abstracts usually written in English. This paper discusses the importance of working with this sub-genre with future researchers and translators during their university years. Two concepts of genre are presented (SWALES, 1990; BATHIA, 1993), as well as an approach on how to introduce academic genre to undergraduate students. After applying this approach to a mini-course about academic writing, we have noted that translation students have been more attentive to the way they deal with texts based on communicative purposes, tasks, target readers and language.